Use prospects forming bacterium slime in oil branch - O. B. Soprunova; Nguen Viet Tien (Юг России: экология, развитие)
In article prospects of use of microbic technologies in oil-extracting and a petroleum-refining industry are considered. The data about allocation forming bacterium slime from the petropolluted objects located in territory of the Astrakhan region is cited.